2009
DOI: 10.1242/jeb.026575
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin enhances oxygen uptake in larval zebrafish (Danio rerio) but only under conditions of extreme hypoxia

Abstract: SUMMARYThe role of hemoglobin (Hb) in O 2 uptake by zebrafish larvae ranging in age from 5 to 42 days postfertilization was assessed under conditions of normoxia, moderate hypoxia and extreme hypoxia. This was achieved by exposing larvae with and without functional Hb to continuously declining oxygen levels (P O2 ) in closed-system respirometers. Exposure to 5% CO for 2-4 h was used to render Hb effectively non-functional in terms of its ability to transport O 2 . Routine metabolic rate (rM O2 ), critical diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
(31 reference statements)
3
41
0
Order By: Relevance
“…; Fig.2) were comparable with those reported in other studies carried out on zebrafish of similar developmental stage and at similar temperatures (Pelster and Burggren, 1996;Barrionuevo and Burggren, 1999;Bagatto et al, 2001;Grillitsch et al, 2005;Rombough and Drader, 2009). By contrast, the present study appears to be the first to report measurements of CO 2 excretion during early development in a fish.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…; Fig.2) were comparable with those reported in other studies carried out on zebrafish of similar developmental stage and at similar temperatures (Pelster and Burggren, 1996;Barrionuevo and Burggren, 1999;Bagatto et al, 2001;Grillitsch et al, 2005;Rombough and Drader, 2009). By contrast, the present study appears to be the first to report measurements of CO 2 excretion during early development in a fish.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, several studies using a variety of experimental approaches have demonstrated that O 2 uptake in developing zebrafish is not dependent on haemoglobin O 2 transport (via RBCs) until at least 12-14d.p.f. (Pelster and Burggren, 1996;Weinstein et al, 1996;Jacob et al, 2002;Rombough and Drader, 2009; see review by Rombough, 2004) even though erythrogenesis is initiated around 15h.p.f. and RBCs containing haemoglobin are present in the circulation by 24h.p.f.…”
Section: Hmentioning
confidence: 99%
See 1 more Smart Citation
“…During early developmental stages, the gills may not be fully developed and so zebrafish larvae use both cutaneous and gill respiration to satisfy metabolic needs for O 2 (Rombough, 2002). In addition, a model has predicted that zebrafish can survive by simple diffusion in air-saturated water without the need of a circulatory system until 42 dpf (Rombough and Drader, 2009). ASR may then become important as a survival strategy in larvae at O 2 tensions closer to anoxia, where reduced activity no longer provides any benefit and an escape response is elicited.…”
Section: Development Of Asrmentioning
confidence: 99%
“…Because early life stage (ELS) is one of the most sensitive life stages to toxicity during the life cycle, ELS tests with fish species are commonly used as routine toxicity tests in risk assessment (OECD 1998;Roex et al 2002). D. rerio was recommended as a model fish species for short-term embryo-larval toxicity testing (OECD 1998), and there are many studies investigating the effects of hypoxia on zebrafish embryo or larvae (Padilla and Roth 2001;Ton et al 2003;Rombough and Drader 2009;Steele et al 2009;Van Rooijen et al 2009;Yaqoob et al 2009). We found that the 7-day-old F 3 vhb transgenic larvae may be suitable for study of the hypoxia tolerance traits.…”
Section: Discussionmentioning
confidence: 99%